Presencia del Gato Montés (Lynx rufus) en selvas tropicales del estado de Hidalgo, México - Valencia-Herverth, Raúl; Valencia-Herverth, Jorge (THERYA, 2012)
We report the presence of the bobcat (Lynx rufus) in the northeastern of the state of Hidalgo, in the municipality of San Felipe Orizatlán, at 156 meters of altitude. One individual male of L. rufus was run over in a dirty road and donated by local people. This record extends the distribution of this species in Hidalgo approximately 118 km to the southwest of previous records and it is the first evidence of the presence of the species in semievergreen tropical forest in the state of Hidalgo, Mexico.